Stepwise Luweero mini-video library of good agricultural and climate-smart practices - International Institute of Tropical Agriculture (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
A set of 13 short (15-30 second) video clips of each of the individual practices that make up the set of recommended good agricultural and climate-smart practices for coffee in Uganda.